Is thyroid nodule location associated with malignancy risk? - Ramundo, Valeria; Lamartina, Livia; Falcone, Rosa; Ciotti, Laura; Lomonaco, Cristiano; Biffoni, Marco; Giacomelli, Laura; Maranghi, Marianna; Durante, Cosimo; Grani, Giorgio (Ultrasonography (Seoul, Korea), 2019)
Nodules located in the upper pole of the thyroid may carry a greater risk for malignancy than those in the lower pole. We conducted a study to analyze the risk of malignancy of nodules depending on location. The records of patients undergoing thyroid-nodule fine-needle aspiration cytology (FNAC) at an academic thyroid cancer unit were prospectively collected. The nodules were considered benign in cases of a benign histology or cytology report, and malignant in cases of malignant histology. Pathological findings were analyzed based on the anatomical location of the nodules, which were also scored according to five ultrasonographic classification systems. Between November 1, 2015 and May 30, 2018, 832 nodules underwent FNAC, of which 557 had a definitive diagnosis. The prevalence of malignancy was not significantly different in the isthmus, right, or left lobe. Among the 227 nodules that had a precise longitudinal location noted (from 219 patients [155 females], aged 56.2±14.0 years), malignancy was more frequent in the middle lobe (13.2%; odds ratio [OR], 9.74; 95% confidence interval [CI], 1.95 to 48.59). This figure was confirmed in multivariate analyses that took into account nodule composition and the Thyroid Imaging, Reporting, and Data System (TIRADS) classification. Using the American College of Radiologists TIRADS, the upper pole location also demonstrated a slightly significant association with malignancy (OR, 6.92; 95% CI, 1.02 to 46.90; P=0.047). The risk of thyroid malignancy was found to be significantly higher for mid-lobar nodules. This observation was confirmed when suspicious ultrasonographic features were included in a multivariate model, suggesting that the longitudinal location in the lobe may be a risk factor independently of ultrasonographic appearance.